Novel technique for the simultaneous isolation of cardiac fibroblasts and epicardial stromal cells from the infarcted murine heart. Issue 5 (16th August 2019) - Owenier, Christoph; Hesse, Julia; Alter, Christina; Ding, Zhaoping; Marzoq, Aseel; Petzsch, Patrick; Köhrer, Karl; Schrader, Jürgen
Abstract: Aims: Myocardial infarction (MI) leads to activation of cardiac fibroblasts (aCFs) and at the same time induces the formation of epicardium-derived cells at the heart surface. To discriminate between the two cell populations, we elaborated a fast and efficient protocol for the simultaneous isolation and characterization of aCFs and epicardial stromal cells (EpiSCs) from the infarcted mouse heart. Methods and results: For the isolation of aCFs and EpiSCs, infarcted hearts (50 min ischaemia/reperfusion) were digested by perfusion with a collagenase-containing medium for only 8 min, while EpiSCs were enzymatically removed from the outside by applying mild shear forces via a motor driven device. Cardiac fibroblasts (CFs) isolated from unstressed hearts served as control. Viability of isolated cells was >90%. Purity of EpiSCs was confirmed by immunofluorescence staining and qPCR of various mesenchymal markers including Wilms-tumor-protein-1. Microarray analysis of CFs, aCFs, and EpiSCs on day 5 post-MI revealed a unique gene expression pattern in the EpiSC fraction, which was enriched for epithelial markers and epithelial to mesenchymal transition-related genes. Compared to aCFs, 336 significantly altered gene entities were identified in the EpiSC fraction. qPCR analysis showed high expression of Serpinb2, Cxcl13, Adora2b, and Il10 in EpiSCs relative to CFs and aCFs. Furthermore, microarray data identified Ddah1 and Cemip to be highly up-regulated in aCFs compared to CFs. Immunostaining of the infarcted heart revealed a unique distribution of Dermokine, Aquaporin-1, Cytokeratin, Lipocalin2, and Periostin within the epicardial cell layer. Conclusions: We describe the simultaneous isolation of viable, purified fractions of aCFs and EpiSCs from the infarcted mouse heart. In this study, several differentially expressed markers for aCFs and EpiSCs were identified, underlining the importance of cell separation to study heterogeneity of stromal cells in the healing process after MI.